SELF-MANAGEMENT EXPERIENCE OF PATIENT WITH TYPE 2 DIABETES IN SUMBAWA BESAR, WEST NUSA TENGGARA: A QUALITATIVE STUDY - Satriya Pranata; Xuan Yi Huang (Universitas Pelita Harapan, 2020)
Background: The number of patients with diabetes mellitus (DM) in Indonesia was reported to increase every year. Indonesia included into ranked sixth countries for diabetes (20-79 years) and ranked third as the deadliest diseases, (IDF, 2017; WHO, 2016). However, research about self-management experience for people with Type 2 DM is insufficient. Objectives: The purpose of this study was to explore the Self-management Experience of Patient with Type 2 DM in Sumbawa Besar, West Nusa Tenggara. Methods: Purposive sampling with one-on-one depth interview were used to obtain the participants experiences about self-management. six participants were selected randomly from 30 participants in community. Data saturation was achieved and analyzed by Colaizzi’s (1978) seven-step method. Results: Six themes emerged from study were: dietary adjustment, using medicine to decrease blood glucose, taking exercise, taking care of DM by oneself, social support and looking for information regarding DM were consider as important theme for DM population in Sumbawa Besar, West Nusa Tenggara. Conclusion: the result of this study showed that each patient with DM has ability to carry out self-management based on their belief, value and knowledge. Basic information about diabetes was the most important aspect before patients can perform self-management successfully.